Growth analysis during the vegetative phase of five phenotypes of copoazú Theobroma grandiflorum (Willd ex Spreng) Schum. in the Colombian western Amazonia (2011)
This research was undertaken on four farms in the department of Caquetá in order to analyze the physiological responses of five copoazu phenotypes from a Sinchi collection in the early stages of growth under different canopy coverings. To create such an effect, an experimental design of blocks was used with five copoazu phenotypes distributed at random. During the period of evaluation, variables of plant height, leaf area, dry mass, and rates of growth were determined. The direct variables increased constantly, especially in size and quantity of dry materials, as well as maintaining leaf area. In contrast, the rates of growth, net assimilation rate, relative growth rate, leaf area index and leaf area ratio presented oscillating values in five ecotypes during the period of evaluation. These results indicated differential behaviour of copoazu in the first phases of growth which indicated an interaction of a genotype with an environment reflected in the different behaviours of physiological determinants of the plant and providing evidence of certain plasticity in phenotypes, according to each of the covers, the best of which under 15% coverage. The ecotypes 4 and 11 differed from the other ecotypes presenting better adaptability in all sites independent of the percentage of cover. Previous studies showed that, according to their morpho-agronomic characteristics, these ecotypes present a high productivity and are included in the group characterised by different levels of tolerance to the attacks of witch broom (Crinipelis perniciosa).